How social housing policies affect housing quality and affordability?: The European case - Melo, Gonçalo Martins de (2021)
This dissertation analyses the impact of the share of social housing stock on indicators of housing affordability and housing quality. The model covers a panel of 24 European countries between 2009 and 2019. The results suggest that although there is no statistically significant relation between the share of social rental dwellings and severe housing deprivation rate, there is a positive effect of social housing on housing affordability. An increase of one percent in the share of social housing leads to an increase of 0.94% on households without financial burden due to housing costs. The countries with the highest levels of households without financial burden due to housing costs are also among those with the highest levels of social housing, and the countries with the lowest levels of this indicator are among the countries with the lowest levels of social housing. The main contributions of this research are the time considered throughout the analysis and its population. Despite the difficulty in finding the impact of social housing on households' wellbeing, this analysis portraits many European countries, as well as takes into consideration recent data on social housing, never considered.